Konseling Individu dengan Teknik Rational Emotive Behavior Therapy (REBT) dalam Mengatasi Perilaku Toxic pada Remaja di Desa Mangku Negara - Sepian Dista (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to determine the effectiveness of individual counseling using Rational Emotive Behavior Therapy (REBT) in overcoming toxic friendship behavior in adolescents. Toxic friendship behavior is a pattern of friendship characterized by a tendency to belittle, envy, emotionally depend on, and show a lack of empathy towards friends. The subject of this study is a teenager with the initials “A” who experiences various symptoms of toxic friendship, such as envy of friends' achievements, difficulty accepting criticism, and excessive emotional dependence. This study uses a descriptive qualitative approach with a case study method. The intervention process was conducted through individual counseling using the REBT technique, which consists of five stages of the ABCDE model: Activating Event, Beliefs, Consequences, Disputing, and Effective New Beliefs. Counseling was conducted in four sessions for one month. The results of the study indicate that individual counseling using REBT techniques is effective in reducing toxic friendship behaviors in clients. Clients experienced positive changes, such as being able to appreciate their friends' achievements, being more open to feedback, managing their emotions more healthily, and no longer relying solely on friendships for happiness. Additionally, clients demonstrated a decrease in negative emotional symptoms such as jealousy and excessive fear. REBT techniques were found to assist clients in identifying and replacing irrational thoughts with more logical and rational patterns of thinking. As a result, this technique can serve as an effective alternative in counseling services for adolescents facing challenges in their social relationships. Konseling individu, Rational Emotive Behavior Therapy (REBT), toxic friendship